2020
DOI: 10.1016/j.jmig.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Shaving for Bowel Endometriosis

Abstract: Study Objective: To demonstrate laparoscopic shaving of deeply infiltrative endometriosis affecting the rectosigmoid colon, with particular emphasis on the anatomic and technical aspects of the procedure. Design: Stepwise demonstration of the technique with narrated video footage. Setting: Intestinal involvement in deep endometriosis is estimated to occur in 8% to 12% of patients, with 90% of occurrences being located in the colorectal segment. Deep endometriosis of the rectosigmoid is defined as endometriosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The proposed method may also play a role in reducing the number of patients undergoing a segmental bowel resection. We agree with all these aspects, and despite this modification requiring further evaluation, as mentioned by the authors, it is a very promising technique and improves the surgical management of deep endometriosis (DE) with rectal involvement (2). DE is the most severe type of endometriosis, and it affects the bowel in up to 25% of cases and is frequently associated with dyspareunia, dysmenorrhea, and a reduced quality of life (3,4).…”
supporting
confidence: 62%
“…The proposed method may also play a role in reducing the number of patients undergoing a segmental bowel resection. We agree with all these aspects, and despite this modification requiring further evaluation, as mentioned by the authors, it is a very promising technique and improves the surgical management of deep endometriosis (DE) with rectal involvement (2). DE is the most severe type of endometriosis, and it affects the bowel in up to 25% of cases and is frequently associated with dyspareunia, dysmenorrhea, and a reduced quality of life (3,4).…”
supporting
confidence: 62%
“…Bowel endometriosis is a complex gynecologic condition that requires targeted investigation and multi-disciplinary care by an experienced team 1 . Here, we demonstrate the value of the pre-operative transvaginal sonography in the assessment of deep endometriosis involving the bowel.…”
Section: Manuscriptmentioning
confidence: 99%
“…Rectal shaving is well suited for smaller lesion (typically <3 cm) without entering the bowel lumen. 2 Recently, Donnez and Roman concluded that surgeons should consider rectal shaving as first-line surgical treatment of deep endometriosis, irrespective of nodule size or association with other digestive sites. 3,4 The goal of this paper is to review the available literature on shaving technique in terms of complications and recurrence comparing it with other techniques.…”
Section: Introductionmentioning
confidence: 99%